Metode Life Cycle Assessment (LCA) Sebagai Penilaian Terhadap Dampak Lingkungan pada Proses Produksi Pupuk ZA II Petrokimia Gresik - Aussie Amalia; Bagas Chrisma Pratama (Prosiding ESEC, 2023)
Petrokimia Gresik is one of the largest and most comprehensive fertilizer companies in Indonesia, playing a major role in the food security sector. The superior fertilizer production is ZA II fertilizer. The existence of a strong concern lies in the emissions produced in the production process where the presence of gas can trigger environmental impacts if not properly managed and controlled. Therefore, through methodLife Cycle Assessment (LCA) is able to identify and assess potential environmental impacts in PT Petrokimia Gresik's ZA II fertilizer production process. Approach done byEndpoint divided into human health, ecosystem quality, and natural resourcesRecipe 2016. As a support for the identification carried out, software will be used in the form of Open LCA type 1.11.0 and SimaPro type 9.4.0.2. The studies obtained show that there is a unit process that is produced with the greatest impact on the drying unit system (drying) and cooling (cooling) due to the causes of the chemicals used and the emission content released in the form of ammonia (NH3) and carbon dioxide (CO2). With this impact, it is necessary to carry out alternative solutions to reduce the risk of impacts that occur in the ZA II fertilizer production process.